OXIDATIVE STRESS IN THE DEVELOPMENT OF POSTPARTUM ENDOMETRITIS AND ITS PROGNOSTIC SIGNIFICANCE - Kamilova Iroda Abdurasulovna; Umarov Aziz Rustamovich (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Abstract. The development of postpartum endometritis is characterized by an aggravated obstetric-gynecological, somatic, and social history, as well as a postpartum history with high levels of proinflammatory markers. The quality of the predictive ability of the models was assessed using the Nagelkerke determination coefficient R². R² for an increase in MDA concentration is 85.67%; and for a decrease in AOS activity, it is 93.52%, which proves the higher prognostic significance of the obtained regression models.